PERANCANGAN APLIKASI SISTEM INFORMASI AKUNTANSI BERBASIS WEB DI TOKO KARTIKA MOTO - Muhamad Dody Firmansyah; Kelvin (P3M Institut Teknologi Pagar Alam, 2022)
Web-Based Accounting Information System Design at Kartika Motor. This study aims to determine the accounting information system used by Kartika Motor and designing a web-based accounting information system that can be implemented and in accordance with Kartika Motor's needs. This research is a research on designing an accounting information system with the Waterfall mode method which consists of five phases, namely requirements, design, development, testing and maintenance. Data obtained through literature study and interviews. The result of this research is a web-based information system on Kartika Motor. Functions related to cash receipts include the sales function, inventory function, and recording function. Kartika Motor does not yet have a clear internal control and division of tasks. The documents used are cash notes and invoices, while the notes made are cash sales records, accounts receivable, and inventory. However, recording is not carried out routinely so that the availability of information regarding these records is very limited and inaccurate. Based on these data, a web-based cash receipt accounting information system design was made using the waterfall method. The business modeling stage produces the data needed for system design. The data modeling stage produces a data table and its relationship in the form of a waterfall. The process modeling stage produces context diagrams, DFDs, process diagrams, and program interface designs. The application generation stage produces design changes into the programming language. And the testing and turnover stage produces a prime process that is ready to be implemented. The research has many positive impacts where the owner of Kartika Motor provides convenience in accounting records, accounting records are more effective and efficient and can generate financial reports automatically.